Website-Based Learning Media Using Glideapps in Economics Subjects Material National Income and Economic Inequality Class XI SMAN Kalisat Jember Regency - Fitriana, Nur Faricha; Suharso, Pudjo; Mardiyana, Lisana Oktavisanti (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2024)
This research aims to create a web-based learning media using Glideapps that is suitable and attractive for the topics of national income and economic disparity for 11th-grade students at SMAN Kalisat, Jember Regency. The research is limited to the development stage, using the Four-D model. Research instruments include media validation sheets and student response questionnaires. Data analysis is conducted through feasibility and attractiveness tests. The results of the study indicate that the developed learning media is considered feasible, with material validation scores of 91.4%, media validation scores of 93.3%, and language validation scores of 92%, all falling into the highly feasible category. The media also exhibits high attractiveness, with a trial percentage of 89.5% for the limited group and 90.3% for the extensive group, indicating its high level of appeal. Thus, website-based learning media using glideapps can be used as a means of a new and interesting learning process to raise students' enthusiasm for the learning process, especially on the material National Income and Economic Inequality.